2017
DOI: 10.1017/s1478951517000190
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative study of the emotional and spiritual needs of Hispanic families in hospice

Abstract: Our results provide insight into the specific emotional and spiritual needs of Hispanic families receiving hospice services. Our findings highlight that cultural values play an important role in the hospice care experiences of Hispanic families.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 29 publications
(35 reference statements)
0
15
0
Order By: Relevance
“…For example, a recent qualitative study of Hispanic families in hospice revealed a strong desire among patients and caregivers for education to understand the dying process and medical options. 8 Despite this desire from patients, providers often report reluctance to discuss end-of-life issues. Explanations for this reluctance often include a focus on providing life-sustaining treatment, a lack of confidence with prognoses, lack of time, and concerns about distrust from patients.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a recent qualitative study of Hispanic families in hospice revealed a strong desire among patients and caregivers for education to understand the dying process and medical options. 8 Despite this desire from patients, providers often report reluctance to discuss end-of-life issues. Explanations for this reluctance often include a focus on providing life-sustaining treatment, a lack of confidence with prognoses, lack of time, and concerns about distrust from patients.…”
Section: Introductionmentioning
confidence: 99%
“…AIDS patients in South Africa commented that their experience with hospice staff was superior their interaction with hospital staff (Makhele & Mulaudzi, 2012). Across cultures, participants liked when staff were friendly and approachable, conversed with patients and family members, knew the names of their family members, and engaged in social appropriate physical contact such as hand-shaking and hugging (Bray & Goodyear-Smith, 2013; Kataoka-Yahiro et al., 2016; Nuñez et al., 2017; Slater et al., 2015). The Maori appreciated the ability to contact their hospice staff after hours, which prevented them from having to go to the emergency room when they had questions or problems with symptom control (Slater et al., 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Religious beliefs played an important role in end-of-life care, impacting perceptions of hospice and decision-making. African American and Hispanic patients strongly associated enrollment in hospice with a lack of faith in God (Dillon & Basu, 2016; Noh, 2014; Nuñez et al., 2017; Thienprayoon et al., 2016). Some African American families chose to reframe hospice as accommodating God’s will when religious leaders provided an endorsement (Dillon & Basu, 2016; Kidd et al., 2018; Noh, 2014).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations